Large eddy simulation on the effect of free-stream turbulence on bypass transition - Xu, Zhengqian; Zhao, Qingjun; Lin, Qizhao; Xu, Jianzhong (The International journal of heat and fluid flow, 2015)
[Display omitted] •Low-frequency dominant inflow leads to inner instability.•High-frequency mode is indispensable for inner instability.•Low-frequency mode highly affects the transition onset.•High-frequency mode highly affects the transition rate.•The frequency of laminar streaks is comparable with that of turbulent spot. The effect of free-stream turbulence (FST) on bypass transition in a zero-pressure-gradient boundary layer is investigated by means of Large Eddy Simulation (LES). The broadband turbulent inflow is synthesized to validate the feasibility of LES. Both a zero-thickness plate and one with super-ellipse leading-edge are addressed. The calculated Reynolds-averaged fields are compared with experimental data and decent agreement is achieved. Instantaneous fields show the instability occurs in the lifted low-speed streaks similar to earlier DNS results, which can be ascribed to outer mode. Various inflows with bi-/tri-mode interaction are specified to analyze effects of particular frequency mode on the instability pattern and multifarious transition or non-transition scenarios are obtained. Outer instability is observed in the cases with one low-frequency mode and one high-frequency mode inflow as reported by Zaki and Durbin (2005), and with one more high-frequency mode appended. Inner instability is observed in the case with a low-frequency dominant inflow, while the high-frequency mode is indispensable to induce the secondary instability. Furthermore, the results show that the transition onset is highly sensitive to low-frequency mode while the transition rate is highly sensitive to high-frequency mode. Finally, the formational frequency of turbulent spot (FFTS) is counted and the frequency of laminar streaks is demonstrated by spectral analysis.